Sources of FDI flows to developing Asia: The roles of distance and time zones - Rabin Hattari; Ramkishen S. Rajan (Asian Development Bank Institute (ADBI), 2008)
This paper investigates sources and determinants of foreign direct investment (FDI) flows to developing Asia using bilateral FDI flows for the period 1990-2005. The Triad (composed of Japan, EU, and the US) has accounted for about 35-40% of FDI inflows to developing Asia in recent years, with Japan being the single largest investor. Intra-developing Asian flows have also accounted for about 35% of total inflows to the region, and these shares have remained fairly stable for the period 1997-2004. With regard to the determinants of FDI flows, the paper finds that an augmented gravity model fits the data fairly well. We pay particular attention to possible differences in the determinants of FDI flows to developing Asian economies from the rest of the Asia and Pacific region, compared to those from nonregional OECD economies, with an emphasis on the roles of distance and time zone differences. To preview the main conclusion, we find that the elasticity of distance is greater for FDI from the non-Asia Pacific OECD economies than intraregional Asian flows. However, this difference disappears when one accounts for differences in time zones.
Keywords: F21; F23; F36; 330; Direktinvestition; Ausländisch; Gravitationsmodell; Schätzung; Asien